Bioremoval of Chromium by Local Isolates of Pseudomonas aeruginosa in Respect to its Genotype - A. Hameed, Qusay; Abdulhay, Hind S. (Iraqi Journal of Science, 2023)
The current study included bioremoval of chromium metal ions from aqueous solution by using seventeen Pseudomonas aeruginosa species isolated from different environments. The experimental results showed that isolates Pseudomonas aeruginosa have high efficiency in removal of chromium where the P. aeruginosa p.8 was the most efficient (P≥0.001) in bioremoval of chromium with a removal capacity reached 92.5 mg/L and removal index reached (96.5%). While P. aeruginosa p.4 was the least efficient (P≥0.001) in bioremoval of chromium from aqueous solutions reached 74.6 mg/L and removal index reached (79.8%). The REP-PCR detection using BOX-primer, showed genetic relatedness among the isolates of P.aeruginosa. The isolates were grouped according to the REP-PCR to different genotyping, named clusters which included C1, C2, C3 and C4 with relatedness: 2 (88%), 2 (73%), 4 (73%) and 2 (77%), respectively. The REP-PCR analysis showed that the genetic relatedness between isolates regarded to the source of the isolation as well as their efficiency of bioremoval process.